Cancer immune contexture and immunotherapy. (April 2016) - Becht, Etienne; Giraldo, Nicolas A; Dieu-Nosjean, Marie-Caroline; Sautès-Fridman, Catherine; Fridman, Wolf Herman
Highlights: The immune contexture is a powerful tool to predict patient's prognosis. The prognostic impact of TILs is modulated by other stromal components. The immune contexture and its prognostic impact is reproduced in metastases. Carcinogenesis pathways influence the immune contexture and its impact. Classification in three immune subgroups and may guide immunotherapies. Abstract : The immune contexture that characterizes the density, the location, the organization and the functional orientation of tumor-infiltrating immune cells in cancers has a clinical impact on patient's outcome. It is, in great part, shaped by the malignant cells, as in a given cancer type, tumors presenting different oncogenic processes have different immune contextures. Moreover, the immune contexture in metastatic sites reflects that of the corresponding primary tumors. Finally, the components forming the immune contexture represent targets and markers of efficient anti-cancer immunotherapies.